ASSESSMENT OF PRODUCTIVITY OF IRRIGATED MEADOW-ALLUVIAL SOILS - Gulchehra Sodikova; Nilufar Meyliyeva; Mahliyo Ollaberganova (Journals Park Publishing, 2023)
The article describes the state of fertility of irrigated meadow-alluvial soils. It contains information on the morphogenetic indicators of meadow-alluvial soils, the amount of humus and nutrients. The amount of humus and nutrients in these soils was observed to be low during the research.
Keywords: Irrigated meadow-alluvial soil, humus and nutrients, morphological characteristics, soil fertility.